Effect of garlic supplementation on the humoral and cellular immunity after immunization of broilers by sonicated oocysts of Eimeria tenella - Latif, I. K.; H., Awse Al. (Journal of Kerbala for Agricultural Sciences, 2017)
This study was performed to investigate the effect of garlic with sonicated oocysts immunization of E. tenella on humoral and cellular immune responses in broilers. A total of 150 broiler chicks were divided into 6 equal groups. The 1st and 2nd groups inoculated in ovo with sonicated oosycts of E. tenella and repeated by I/M injection at day 14 .The 3rd and 4th groups injected I/M with sonicated oosycts at day old and repeated at day 14, the 1st and 3rd feeding a basal diet, while the 2nd, 4th and 5th groups feeding basal diet with garlic. The birds of the 6th group fed basal diet and remains as control. All groups were challenged with 50,000 of sporulated oocysts of E. tenella. The results revealed that the immunized groups and immunized with garlic have a significant difference P < 0.05 in the lymphoid organs weight and indices, antibody titers against SRBCs (sheep red blood cells) and Phytohaemagglutinin (PHA) skin test in camper with control and garlic groups specially at day 35. At these instants there was no significance difference between the two procedures of immunization in ovo and I/M. In conclusion that in ovo and I/M immuinzation of sonicated oocyst showed some evidence of reducing negative performance impact associated with coccidiosis.